Reflexive mentality: an approach of advanced management within the framework of the information society (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2017)
The purpose of this article is to present some ideas about how the development of the reflective mentality affects the efficient performance of a manager, both in the creation of a personal project, as well as in the functions he performs within an organization. Companies require managers with creativity, open to innovation who are able to see the outside through their own reflection, which is achieved when you start to manage the "me". Starting from this perspective, the manager with a high level of self-knowledge is located in an emerging scenario called the information society, and the advantages offered by the crossing of reflexive thinking with practical action are presented, in order to give an adequate use to the advances technological This seeks to promote reflection, in the people who run an organization, ie stop to think about the existing reality, what they have and everything they need, in order to maintain a balance to ensure progress towards advanced management.
Keywords: advanced management; reflective mentality; information society